Przestrzenne zróżnicowanie częstości wypadków komunikacyjnych w Polsce w latach 1999-2004 - Wieteska-Rosiak, Beata (Spatial Diversity in Communication Accidents Frequency in Poland Between 1999 and 2004, 2008)
Fast motorization development caused on the one hand road traffic increase and on the other hand communication accidents increase. One way of removing communication accidents are non-life insurances. In the work there is a trial of the whole look at the traffic safety on the regional scale. On the basis of available data it is possible to look at the traffic safety through many different accident frequency indexes. There is the conclusion that the accidents frequency definition can be explained in different ways. Accepted ranking method of the provinces with the highest and nearest indexes points two spheres, in which there should be included reductions and rises in the traffic insurance premiums. Provinces ranking shows that the most save province regarding investigated topic is Podkarpackie province. The highest insurance premium is suggested for Świętokrzyskie province (this is the most dangerous province).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 484-491